Geometric Design Optimization for Dynamic Response Problems of Continuous Reinforced Concrete Beams - Sharafi, P; Hadi, M. N. S; Teh, Lip H (Journal of computing in civil engineering, 2014)
AbstractThis paper presents a computer-aided design method for conceptual geometric layout optimization of multispan RC beams for any type of dynamic responses. A key feature of the paper is the development of a new cost-optimization method for geometric layout problems that take both cost parameters and dynamic responses into account to achieve an optimum design along with acceptable dynamic performance of RC beams. This method takes advantage of employing a new optimization formulation that considerably simplifies the preliminary layout design computations. It focuses on minimizing the structural cost subject to constraints on eigenfrequencies, modal shapes, and the static and dynamic equilibrium. The proposed structural optimization problem is solved employing an ant colony optimization (ACO) algorithm. To verify the suitability of the methodology and illustrate the performance of the algorithm, solved examples are presented.